(3CQLhRI aj GSe GdaGYds - (3GdeZfjSGhj , CMeO Hf eMeO,J (B1090 (3g` s
(3ChdgG (B:s
(3CMeO QHG NGdb GdHQGjG HGSW GdQRb heLRd GdYWGjG s
(3BNQgG (B:s
(3haGYd eG Chd aGYde Hg ef Cf haYd BJi adP Hg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B159 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B16 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdfMhs